A signal-on electrochemical DNA biosensor based on exonuclease III-assisted recycling amplification. Issue 48 (30th November 2022) - Yu, Xiongtao; Jiang, Bowen; Wang, Lishi
Abstract : A signal-on electrochemical DNA biosensor was constructed for MnSOD gene detection by incorporating electrodeposited AuNPs and exonuclease III-assisted target recycling signal amplification strategy. Abstract : DNA electrochemical detection technology has attracted tremendous interest in recent years. However, a facile and sensitive method for the detection of the disease indicators or genes is still waiting. Herein, we constructed a signal-on electrochemical platform for detecting the manganese superoxide dismutase (MnSOD) gene by incorporating a redox electrochemical signal probe (methylene blue) and exonuclease III-assisted target recycling signal amplification strategy. The sensor was prepared by self-assembly of a capture DNA probe of thiol-modified on GCE with gold electrodeposition. In the presence of target DNA, the exonuclease III can cleave the duplexes formed by the target DNA and the redox-labeled hairpin probes, release the target DNA and produce a residual sequence. The target DNA can continue to hybridize with the hairpin probe for the next cycle of amplification. The residual sequence hybridized with the surface-immobilized capture probes on AuNPs-modified GCE to generate a significantly amplified redox current. In particular, the redox current value of the resultant sensor showed a linear relationship with MnSOD gene concentration in the range of 1–10 4 pM with the detection limit as low as 0.3 pM. Furthermore, the sensor has excellent specificity and can distinguish single-base mismatch from perfectly matched target DNA. The sensor is fast in operation, and simple in design for detecting different DNA sequences or DNA identification by selecting the appropriate probe sequence, thus shedding light on a good promising application when encountering disease outbreaks or for the early clinical diagnosis of gene-related diseases.